Development of a systems-level design language - Tyler, B. J. (Nazarbayev University, 2014)
This project will result in design tools and technologies that will facilitate the creation of complex, heterogeneous systems that meet requirements. From a more pure-research perspective, this project will also lay the foundation for further work into modeling language development and the application of verification and validation techniques to system design.
Keywords: design language; hardware systems; real-word systems; elaboration; project